Manajemen Komunikasi Dalam Menyosialisasikan Pencegahan Stunting Di Kecamatan Lebak Wangi Kabupaten Serang Tahun 2023 - Devin Syahputra; Annisarizki Annisarizki; Siska Mardiana (Universitas Serang Raya, 2024)
Problems: Stunting is a health disease that causes chronic growth and development failure in toddlers whose nutritional needs are not met. Stunting also causes other health conditions such as intellectual disorders, motor nerve disorders, and immune disorders. Purpose: This research aims to determine the planning, organization, implementation and evaluation of Lebak Wangi Regency in socializing stunting prevention. Methodology: This research uses a qualitative approach with a case study method. This research data was obtained from observations and interviews with 6 informants in Lebak Wangi SubDistrict. Results/Findings: The results of this research provide information regarding the planning of Lebak Wangi Regency in socializing stunting prevention, namely mini workshops or coordination with government officials in order to strengthen Lebak Wangi cross-sectors in discussing stunting and conducting research on socialization participants. preventing stunting. Organizing, namely forming an evaluation monitoring team, determining direct communication methods. Implementation includes conducting outreach, implementing a healthy kitchen program to overcome stunting, and providing additional food and using face-to-face communication. Evaluation is a mini/coordination workshop that brings together administrators in the Lebak Wangi Regency area which is held every 3 months after the implementation of stunting prevention outreach activities and the achievement of the stunting prevention outreach program.